Managing Diabetic Eye Disease in Clinical Practice - Singh, Rishi P. (Springer International Publishing : Imprint: Adis, 2015)
This handbook is an overview of the diagnosis, treatment and long-term management of diabetic retinopathy, within the context of overall long-term diabetes disease management. Diabetes-related eye damage (diabetic retinopathy) is one of the most common complications of diabetes, affecting approximately 30-40% of people with diabetes. The situation is so severe that in countries such as the US and UK, diabetic retinopathy is currently the leading cause of blindness in people age 20 to 74 years old. Fortunately, there are several existing and emerging treatments on the horizon and with adequate control of the underlying diabetes, this condition can be successfully managed.